Ride with me - Ride-sharing application with opportunistic AI - Teh, Ming En (2023)
This project is to create an in-house ride sharing application, Ride with ME for UTAR-Kampar campus. It applies opportunistic AI to optimise the scheduling of riders to passenger efficiently. The app is developed by using Flutter and the opportunistic AI algorithm that developed will assist in predicting the user’s daily schedule of location visit based on the user’s Google Maps’ data and thus, matching the driver and passengers intelligently. This will assist a lot of students from UTAR Kampar campus that indeed need a helping hand in transportation problem.